Survivability of single mother: a study in Sepang, Selangor / Mohd Ramlan Mohd Arshad, Fatimah Az Zahrah Alias and Aiza Aqira Marhalim - Mohd Arshad, Mohd Ramlan; Alias, Fatimah Az Zahrah; Marhalim, Aiza Aqira (Universiti Teknologi MARA, Cawangan Melaka, 2018)
The aim of this study is to explore the antecedents for survivability of single mother with the main objectives are exploring the relationship between the variables namely financial burden, employment struggle, mental pressure and social stigma toward single mother survivability and derive the main factor that affect their survivability. 200 respondents of this study are single mother lived in Sepang, Selangor. Purposive sampling technique was used with questionnaire as the instrument. Correlation and regression analysis were conducted, and the findings show that there is significant relationship between the variables and survivability of single mother with financial burden as the main factor. Hence, various parties such as authority, non-governmental bodies and community benefited from the study.